Metal toxicity exposure in Alzheimer's disease - literature review - Jakubowska, Eliza; Hoppe-Mitera, Ewa; Sionek, Irena; Ślemp, Julia; Pakuła, Anita; Kuźma, Krzysztof; Bierć, Karolina; Grochowska, Marcelina; Kisiel-Cybula, Ewelina; Adamowicz, Arleta (Journal of Education, Health and Sport, 2024)
Introduction and purpose: As the elderly population grows, the risk of cognitive decline and dementia increases. Environmental toxicants, including metals, have been identified as potential contributors to these conditions. This literature review investigated the potential contribution of metals, such as aluminium, lead, zinc and copper to Alzheimer's disease development. Material and methods: The literature was conducted using "Pub Med" and "Google Scholar" databases with the keywords "metals", "Alzheimer's disease", "aluminium", "lead", "neurodegenerative diseases", "copper". Brief description of the state of knowledge: Metals can negatively affect the functionality of the central nervous system, leading to impairments in behavior, motor skills, and cognitive abilities. The development of Alzheimer's disease can be influenced by several factors, including Aβ aggregates, tau tangles, synaptic dysfunction, inflammation, and oxidative stress, which may be worsened by interactions with these metals. Results and conclusions: Extensive research has shown a link between metal exposure and neurodegeneration. Understanding the role of metals like lead, copper, aluminum, and zinc in Alzheimer's disease pathogenesis remains crucial, but further investigation is needed. A better insight into the impact of metal exposure on brain health could help find the way for effective prevention and treatment strategies for neurodegenerative diseases.